Thoracotomy for esophageal foreign body removal in a dog - Flores, Fabiano da Silva; Cassanego, Guilherme Rech; Costa, Eliesse Pereira; Rosa, Carolina Cauduro da; Pigatto, Anita Marchionatti; Corrêa, Luís Felipe Dutra (Seven Editora, 2023)
In the clinical routine of small animals, the occurrence of foreign bodies (FB) in the digestive tract is routine, especially in dogs and cats with uncontrolled eating habits and puppies. In dogs, the main occurrence is bones, and in cats, linear materials.  Surgical removal is usually the effective method in the treatment of esophageal FB, and endoscopy is the technique of choice, however, in some cases, it is recommended to perform thoracotomy with esophagotomy, as it presents the best results in surgical resolution. The objective of this study is to report the case of a two-year-old Labrador canine who was treated by the Ophthalmology and Surgery Sector of the University Veterinary Hospital of the Federal University of Santa Maria (HVU-UFSM) and who presented esophageal obstruction by the body and tranche. After the diagnosis and with the results of the complementary comb exams,  the patient was submitted to thoracotomy with esophagotomy for the removal of the FB.  In the intraoperative period,  analgesic, anti-inflammatory, and antibiotic medications were used, as follows: dipyrone 25 mg/kg, TID, tramadol hydrochloride  4 mg/kg, TID, meloxicam 0.1 mg/kg SID and ceftaroline 30 mg/kg BID, all intravenous lines. On the third day after surgery, the patient was discharged without complications. The same medications were prescribed for home administration, replacing the route of administration for the oral route and the antibiotic for cefalexin 30mg/kg. The surgical approach chosen for the treatment was indicated by the size and location of the FB in the esophagus. Thus, it is concluded that the use of this technique provides the removal with the visualization of the viability of the layers and sofic and demonstrates excellent results with a return to routine activities. DOI:https://doi.org/10.56238/alookdevelopv1-020